Transcatheter closure of postsurgical ruptured sinus of valsalva with amplatzer duct Occluder II AS™ device - Cristina Capogrosso; Giuseppe Santoro; Mario Giordano; Maria Giovanna Russo (Wolters Kluwer Medknow Publications, 2018)
Sinus of Valsalva (SV) rupture is a rare, cardiac complication after surgical repair of complex congenital heart disease. This paper reports a 4-year-old male child with double outlet right ventricle (RV) and pulmonary stenosis with superior-inferior arrangement of the ventricles, who was submitted to surgical repair using the "reparation a l'etage ventriculaire" procedure. A few months after an uneventful surgical repair, his clinical condition abruptly worsened because of the rupture of the right SV into the RV outflow tract resulting in large left-to-right shunt and RV functional impairment. To avoid surgical re-do, this late-onset complication was successfully treated by transcatheter implantation of an Amplatzer Duct Occluder Type II Additional Size™ (ADO-IIAS, St. Jude Medical Inc., St. Paul, Minnesota, USA) device.